Simulating 2,4,6-trinitrotoluene (TNT) elimination in a pond inhabited by freshwater algae of the Rhizoclonium genus - Khromykh, N. O.; Хромих, Н. О.; Marenkov, O. M.; Маренков, О. М.; Sharamok, T. S.; Шарамок, Т. С.; Anishchenko, A. O.; Аніщенко, А. О.; Yesipova, N. B.; Єсипова, Н. Б.; Nesterenko, O. S.; Нестеренко, О. С.; et al. (Oles Honchar Dnipro National University, 2023)
Military operations over large areas of Ukraine lead to release of explosives and their derivatives into the environment with subsequent accumulation in natural and artificial water bodies, which unwittingly serve as reservoirs for collecting pollutants from the catchment area. The need to restore aquatic ecosystems dictates the search for efficient, cost-effective and environmentally friendly methods for the elimination of explosives, which corresponds to the processes of biological treatment. In this work, we examined the ability of common freshwater algae of the genus Rhizoclonium to detoxify 2,4,6-trinitrotoluene (TNT) under model conditions of water pollution (at a TNT concentration of 100 mg/L). The exposure time of the algae to TNT was 48 hours, during which the content of TNT and nitrites in the aqueous medium was monitored, as well as the content of chlorophyll and the activity of glutathione S-transferase in plant tissues. 2,4,6-trinitrotoluene was extracted from the aqueous medium with toluene, followed by separation in a separatory funnel, removal of residual water with sodium sulfate, and reduction of the extract volume using a rotary evaporator. The decrease in the concentration of TNT, established by GC-MS technique, was 66.4% by the end of the experiment, while the content of nitrites increased almost 15-fold. In the algae cells, a threefold increase in the enzymatic activity was observed already in the second hour of exposure, followed by a gradual decrease and maintenance at a level of 50% of the control until the end of the experiment. The total chlorophyll content increased significantly from the sixth hour of exposure to the end of the experiment due to an increase in the content of chlorophyll b. The results obtained indicate the efficient biodegradation process and prospects of using algae of the genus Rhizoclonium for cleaning water bodies contaminated with TNT. Військові дії на великих територіях України призводять до викидів вибухових речовин та їх похідних у навколишнє середовище з подальшим накопиченням у природних та штучних водоймах, які мимоволі служать резервуарами для збору забруднюючих речовин із водозбірної площі. Необхідність відновлення водних екосистем диктує пошук ефективних, економічно вигідних та екологічно чистих методів знищення вибухових речовин, що відповідає процесам біологічного очищення. У роботі досліджено здатність звичайних прісноводних водоростей роду Rhizoclonium детоксикувати 2,4,6-тринітротолуол (тротил) у модельних умовах забруднення води (при концентрації тротилу 100 мг/л). Тривалість впливу тротилу на водорості становила 48 годин, протягом яких контролювали вміст тротилу та нітритів у водному середовищі, а також вміст хлорофілу та активність глутатіон-S-трансферази в тканинах рослин. 2,4,6-тринітротолуол екстрагували з водного середовища толуолом з подальшим розділенням у ділильній лійці, видаленням залишків води сульфатом натрію та зменшенням об’єму екстракту на роторному випарнику. Зменшення концентрації тротилу, встановлене методом ГХ-МС, до кінця досліду становило 66,4 %, а вміст нітритів збільшився майже у 15 разів. У клітинах водоростей вже на другій годині експозиції спостерігалося триразове підвищення ферментативної активності з наступним поступовим зниженням і підтримкою на рівні 50% від контролю до кінця досліду. Загальний вміст хлорофілу суттєво зростав із шостої години експозиції до кінця досліду за рахунок збільшення вмісту хлорофілу b. Отримані результати свідчать про ефективність процесу біодеградації та перспективність використання водоростей роду Rhizoclonium для очищення водойм, забруднених тротилом.
Моделювання елімінації 2,4,6-тринітротолуолу (тротил) у ставку, населеному прісноводними водоростями роду Rhizoclonium
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: decontamination; знезараження; Rhizoclonium; ризоклоній; explosives; вибухові речовини; 2,4,6-trinitrotoluene; 2,4,6-тринітротолуол; aquatic ecosystems; водні екосистеми; biodegradation; біодеградація